Behavior‐partitioned diversity reveals differential habitat values of gardens to butterfly communities. Issue 4 (4th May 2021) - Lo, Fiona H. Y.; Tsang, Toby P. N.; Bonebrake, Timothy C.
Abstract: Diversity metrics, essential for habitat evaluation in conservation, are often based on occurrences records with little consideration of behavioral ecology. As species use diverse habitats to perform different behaviors, reliance on occurrence records alone will fail to reveal environmental conditions shaping the behavioral importance of habitats with respect to resource exploitation. Here, we integrated occurrence and behavioral records to quantify diversity and assessed how environmental determinants shape the behavioral importance of gardens to butterflies across Hong Kong. We conducted standardized butterfly sampling and behavioral observation, and recorded environmental variables related to climate, habitat quality, and landscape connectivity. We found differential responses of diversity and behavioral diversity metrics to environmental variables. Connectivity increased taxonomic richness based on occurrence and flying across records, while temperature reduced richness based on occurrence, settling and interaction records. Floral abundance increased richness based on nectaring records only. No environmental variable promoted the average number of behavioral types observed in each taxon. Our results suggest that connectivity and temperature determine the richness of butterflies reaching gardens, while floral abundance determines whether butterflies use the sites as nectaring grounds via modifying species behaviors. Our study demonstrates the utility in integrating behavioral and diversity data to reveal how environmental conditions shape behavioral importance of habitats.